Respiration, Rather Than Photosynthesis, Determines Rice Yield Loss Under Moderate High-Temperature Conditions - Li, Guangyan; Chen, Tingting; Feng, Baohua; Peng, Shaobing; Tao, Longxing; Fu, Guanfu (Frontiers in Plant Science, 2021)
Photosynthesis is an important biophysical and biochemical reaction that provides food and oxygen to maintain aerobic life on earth. Recently, increasing photosynthesis has been revisited as an approach for reducing rice yield losses caused by high temperature. We find that moderate high temperature causes little damage to photosynthesis but significantly increases respiration. In this case, energy production efficiency is enhanced, but most of this energy is allocated to maintenance respiration, resulting in an overall decrease in energy utilization efficiency. In this perspective, respiration, rather than photosynthesis, may be the primary contributor to yield losses in a high temperature climate. Indeed, the dry matter weight and yield could be enhanced if the energy was mainly allocated into the growth respiration. Therefore, we propose that engineering smart rice cultivars with a high efficient system of energy production, allocation and utilization could effectively solve the world food crisis under high temperature conditions.